Prevalence and relevance of secondary contact sensitizers in subjects with psoriasis - D S Krupashankar; Shakthi R Manivasagam (Wolters Kluwer Medknow Publications, 2012)
Background: Psoriasis may be complicated by contact dermatitis due to an impaired cutaneous barrier. Patch testing helps elucidate sensitizers if any. Aims: To determine the prevalence and relevance of secondary contact dermatitis in subjects with psoriasis. Materials and Methods: Patch testing with Indian Standard Series was done and readings interpreted after 48 and 96 hours. Results: Among 110 subjects 47 (42.7%) showed reactions to at least one antigen. Fifteen (13.6%) reacted to fragrance mix, 10 (9.1%) to nickel sulfate, seven (6.4%) to parthenium, and six (5.5%) to balsam of Peru. Palmoplantar psoriasis was the commonest type of psoriasis patch tested. Fragrance mix was the commonest antigen showing 100% current relevance as an aggravating factor of psoriasis. Cosmetics, beauty preparations, skin and healthcare products followed by topical medications were found to be the most common sources of the patch test positivity. Conclusions: Secondary contact dermatitis is common in patients with psoriasis. Patch testing is necessary to determine the triggering or aggravating antigens in these patients to avoid sensitizers and improve quality of life.